Site-Specific Topoisomerase I-Mediated DNA Cleavage Induced by Nogalamycin: A Potential Role of Ligand-Induced DNA Bending at a Distal Site - Sim, S.P; Pilch, D.S.; Liu, L.F. (Biochemistry, 2000)
Sai Peng Sim, Daniel S. Pilch and LEroy F. Liu